Design of a papain immobilized antimicrobial food package with curcumin as a crosslinker. - Cynthya Maria Manohar; Veluchamy Prabhawathi; Ponnurengam Malliappan Sivakumar; Mukesh Doble (PLoS ONE, 2015)
Contamination of food products by spoilage and pathogenic microorganisms during post process handling is one of the major causes for food spoilage and food borne illnesses. The present green sustainable approach describes the covalent immobilization of papain to LDPE (low density polyethylene), HDPE (high density polyethylene), LLDPE (linear low density polyethylene) and PCL (polycaprolactam) with curcumin as the photocrosslinker. About 50% of curcumin and 82-92% of papain were successfully immobilized on these polymers. After 30 days, the free enzyme retained 87% of its original activity, while the immobilized enzyme retained more than 90% of its activity on these polymers. Papain crosslinked to LLDPE exhibited the best antibiofilm properties against Acinetobacter sp. KC119137.1 and Staphylococcus aureus NCIM 5021 when compared to the other three polymers, because of the highest amount of enzyme immobilized on this surface. Papain acts by damaging the cell membrane. The enzyme is able to reduce the amount of carbohydrate and protein contents in the biofilms formed by these organisms. Meat wrapped with the modified LDPE and stored at 4°C showed 9 log reduction of these organisms at the end of the seventh day when compared to samples wrapped with the bare polymer. This method of crosslinking can be used on polymers with or without functional groups and can be adopted to bind any type of antimicrobial agent.